Segment’s joint in precast tunnel lining design - Jusoh, Siti Norafida (Penerbit UTM Press, 2015)
Tunnel lining design requires an interactive approach as the design is not merely about the strength, but how much the tunnel allows to flexure to overcome the ground movement. When tunnel interacts with soil, stress from the ground is distributed into the structure. In the case of precast segmental bolted tunnel lining, it is critical to investigate the lining joints reaction, as this affects the overall flexural behaviour of tunnel lining. The objective of this paper is to present a discussion on the mechanics response of segmental tunnel lining affected by the segment’s joint. A short review on research works conducted in recent day on joint effect in segment’s joint in tunnel lining is also presented.